Review on the Effect of Microstructure on Gear Contact Fatigue - Ling Chen; Peitang Wei; Huaiju Liu; Caichao Zhu; Jiqiang Li; Huan Yan (Jixie chuandong)
With the increasing requirements of power density，load capacity and service life of gear transmission for aviation，wind power and other equipment，gear contact fatigue failure has become an important bottleneck limiting the service performance and reliability of modern gear equipment，and the material microstructure characteristics determine the fatigue performance of gear and other service parts. Through the surveys of the current related research situation both at home and abroad，the main microstructure features of gear materials such as retained austenite，carbide，grain size and their influence on the contact fatigue performance of gears are introduced. The reported numerical simulations of gear contact fatigue based on microstructure modeling and micromechanics constitutive model are summarized to describe the microscopic mechanical behavior of in gear contact fatigue，and to improve the understanding of the key characteristics and mechanism of gear fatigue. The various contact fatigue failure forms of gears occurred in the engineering practice are expounded in detail，and the main factors affecting the contact fatigue failure of gears，the induced microstructure evolution and degradation of mechanical properties，as well as the potential mechanisms of the gear contact fatigue failure，are analyzed. This review aims to provide the further understanding of the relationship between microstructure evolution characteristics and mechanical property degradation during the service process of gears，as well as the internal mechanism of contact fatigue failure，and providing the reference for anti-fatigue design and manufacturing method of high-performance gears.